The role of open reduction and internal fixation in the treatment of the intercondylar fractures of humerus - Sivaram G. V., Venkata; Prabhakar, Y. V. S. (International Journal of Research in Orthopaedics, 2019)
Background: Inter-condylar fractures represent one of the most complicated and challenging fractures in the upper extremity. The results of managing these fractures non-operatively are limited by failure to get anatomical reduction and early mobilization, which often results in painful stiff elbow and/or pseudo-arthrosis. The objective of this study was to evaluate and analyse the role of open reduction and internal fixation in inter-condylar fractures of distal humerus. Methods: The present study was done in Malla Reddy Institute of Medical Sciences between June 2014 and June 2017. Out of 34 cases of intercondylar fractures of humerus admitted during the period, 25 patients were selected for the study that satisfied our inclusion criteria. Three patients out of those selected could not be included in the study as one had cardiac issues pre-operatively, one refused surgery and one was lost to follow up. Results: Our study included 22 patients, 14 male and 8 female patients. Their average age was 41.4 years. The fractures were classified as per the AO classification. There were B1-3, B2-1, C1-6, C2-5, C3-7 fractures. Both compound and closed fractures were included. All the patients were operated by posterior olecranon Chevron osteotomy approach by a senior faculty member. Twenty two patients who satisfied our inclusion criteria were treated, followed up and the results analyzed using Cassabaum’s scale of elbow function we had 86% of excellent to good results. Our results are comparable with other similar studies. Conclusions: Posterior olecranon approach was found to be of most satisfactory approach by us. It allows good exposure of the joint and the ulnar nerve.